Holidays with Pay - TUC leaflet, 1939 (1939)
1939 1918-1939 "Holidays with Pay - TUC leaflet, 1939" [T0151.jpg], 1939, Trades Union Congress The TUC first began to campaign for a paid holiday for workers in 1911. Following the passing of an International Labour Convention (ILO) on holidays in 1936, lobbying of the Baldwin Government was reviewed. A committee of inquiry report in 1938 recommended the gradual introduction of a statutory right to holidays in July 1938. The Holidays with Pay Act gave workers, whose minimum rates of wages were fixed by trade boards, the right to one weeks holiday per year. The TUC, which was calling for 2 weeks' holiday for all workers, was disappointed in the limited legislation.